2015
DOI: 10.1080/02640414.2014.990486
|View full text |Cite
|
Sign up to set email alerts
|

Key parameters of the swimming start and their relationship to start performance

Abstract: The swimming start is typically broken into three sub-phases; on-block, flight, and underwater phases. While overall start performance is highly important to elite swimming, the contribution of each phase and important technical components within each phase, particularly with the new kick-start technique, has not been established. The aim of this study was to identify technical factors associated with overall start performance, with a particular focus on the underwater phase. A number of parameters were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 18 publications
9
89
1
4
Order By: Relevance
“…Studies reported differences in the passive drag gliding in the two different positions noted earlier (Marinho et al, 2009;Vilas-Boas et al, 2010). Because the Breaststroke start is restricted to one single underwater stroke, swimmers do try to optimise their underwater distance breakout by decreasing the passive drag (Marinho et al, 2009;Naemi, Easson, & Sanders, 2010;Vilas-Boas et al, 2010) and/or enhancing the water entry (Tor et al, 2015). Overall, in the starting parameters, a significant stroke effect was observed, mostly between Backstroke and the remaining swimming strokes.…”
Section: Starting Performancementioning
confidence: 94%
See 4 more Smart Citations
“…Studies reported differences in the passive drag gliding in the two different positions noted earlier (Marinho et al, 2009;Vilas-Boas et al, 2010). Because the Breaststroke start is restricted to one single underwater stroke, swimmers do try to optimise their underwater distance breakout by decreasing the passive drag (Marinho et al, 2009;Naemi, Easson, & Sanders, 2010;Vilas-Boas et al, 2010) and/or enhancing the water entry (Tor et al, 2015). Overall, in the starting parameters, a significant stroke effect was observed, mostly between Backstroke and the remaining swimming strokes.…”
Section: Starting Performancementioning
confidence: 94%
“…Hence, the start and the turn combined account to a total of 31-32% of the time (i.e., nearly one third of a 100-m race time). Studies reported the parameters that swimmers should consider to enhance their on-block (Fischer & Kibele, 2016;Tor et al, 2015;Vantorre et al, 2010) and in-water back start (de Jesus et al, 2013;Takeda, Itoi, Takagi, & Tsubakimoto, 2014). The time at the 15-m mark (main outcome) depends significantly from the takeoff velocity, entry angle, underwater time and distance (Fischer & Kibele, 2016;Vantorre, Chollet, & Seifert, 2014).…”
Section: Contribution Of Start Plus Turn To Final Race Timementioning
confidence: 99%
See 3 more Smart Citations